Search for B → τv and B → Kvv̄ - Browder, T; Li, Y; Rodriguez, J; Yamamoto, H; Bergfeld, T; Eisenstein, B; Ernst, J; Gladding, G; Gollin, G; Hans, R; Johnson, E; Karliner, I; et al. (2001)
An analysis of 9.66 × 106 charged B meson decays which results in a conservative upper limit on the branching fraction B(B → τν) < 8.4 × 10-4. The analysis was slightly modified to establish B(B± → K± νν̄) < 2.4 × 10-4. The method used is optimized for conditions available at Y(4S) experiments, and some application of the method to other rare decay modes with large missing energy was aniticipated.